Memetakan Kualitas Visual Lansekap pada Objek Wisata Alam Candi Gunung Kawi di Tampaksiring – Gianyar - MAHAPUTRA, I GUSTI NYOMAN ADI PRAMANA; SEMARAJAYA, COKORDA GEDE ALIT; YUSIANA, LURY SEVITA (Jurnal Arsitektur Lansekap; Vol.1, No.1, April 2015DO - 10.24843/JAL.2015.v01.i01.p05, 2015)
ABSTRACT Mapping Visual Quality Landscape of Gunung Kawi Temple Tourism Object in Tampaksiring - Gianyar . Visual quality landscape depends not only on the physical characteristics of the landscape, but also on the subjective judgment of the individual observers. Visual quality of the landscape can be assessed from the observer's response after seeing the appearance of an object that would lead to the perception of the observer. The research objective criteria for determining the visual quality of the tourist landscape of "good" in particular tourist landscape Gunung Kawi Temple in Tampaksiring, then the point location will be mapped to facilitate tourists taking photos of documentation to capture every moment of their attractions. Theoretically, this research can be used as well as baseline information in an effort to acquire knowledge related to the visual quality of the landscape, especially regarding the visual quality of tourist landscape. Visual quality of the landscape that " good " that can meet the three areas of professional experts or the general good of the people is “a visual quality that is easily understood when one sees , in a vantage point where the tape contained a story that can provide information in a straightforward , have the impression living / soul / spirit will be able to describe the depth dimension , both visible by eye / recorded by the camera media without departing from the existing context and still refers to the basic rules of photography”.   Keywords : travel gunung kawi temple, visual quality landscape